Fingerprint Doorlock and Home Security System by Using Arduino and IOT - Mohamad Ramlan, Mohamad Farid; Bakar, Lilywati (Progress in Engineering Application and Technology, 2021)
The number of burglary cases are increasing day by day and owners surely don’t want their home to be intruded. So, the aim of this project is to create a security system for home and door-lock with fingerprint detection feature to unlock the door in order to increase the home security and at the same time, it will be more convenient. The components used in this project are Arduino Uno, ESP32-Cam, fingerprint scanner, LDR module, Laser Module and Relay Module. the product of this project should be able to detect and capture the photo of people that stand in front of the door and unlock the door when fingerprint scanner detects the owner fingerprint. There is an improvement should be added in this project for the future which face recognition system to increase the security.